Greenhouse Gas Fluxes and Modelling from Rice Workshop: Report - Adviento-Borbe, M. Arlene; Ferrer, Anaida; Hasegawa, Toshihiro; Li, Tao; Mencos Contreras, Erik; Minamikawa, Kazunori; Radanielson, Ando; Rosenzweig, Cynthia; Sander, Bjoern Ole; Valdivia, Roberto (International Rice Research Institute, 2025)
Methane (CH4) emissions from paddy fields contribute significantly to agricultural greenhouse gas (GHG) emissions, posing a critical challenge for achieving global climate goals. Despite the availability of the Tier 3 method—which utilizes process-based models and high-resolution datasets to capture variability in site-specific CH4 emissions, its application has been limited to a few countries. There is still a large gap in establishing country and regional specific emissions factors and an increasing demand to measure actual emissions from the field. These requirements are not only for country-level inventories to the United Nations Framework Convention on Climate Change (UNFCCC) but also for the emerging carbon market in the agricultural sector. Significant efforts are being invested in advancing technologies and options for targeting and supporting climate mitigation initiatives in rice systems. Measurements and monitoring are critical in setting the baseline for these initiatives and in evaluating the progress made. However, their implementation remains challenging due to limited consensus in protocols for measurements, as well as the limited accessibility of tools and technologies for measurements, modeling and monitoring of emissions.